Relationships between yellow and purple passion fruit variables - Lopes, Beatriz G. (2024)
Brazil is the world’s largest producer of passion fruit, with the species Passiflora edulis Sims (yellow and purple passion fruit) being the most popular commercially. Due to the great economic importance of this culture, seeking high productivity, phytotechnical quality, and maintenance of existing germplasms, among others, it is necessary to carry out studies of the most diverse types of this culture. In this crop, the use of multivariate techniques has increasingly driven studies on genetic differences between passion fruit species. Therefore, this research aimed to identify the variables that deserve greater emphasis in experiments with two commercial species of Passiflora: Passiflora edulis Sims f. edulis (purple passion fruit) and Passiflora edulis Sims (yellow passion fruit), verifying if the species differ from each other. For this purpose, principal component analysis, multivariate analysis of variance (MANOVA), and Hotelling’s T2 test were performed. The principal component analysis proved to be effective, allowing the removal of five variables for yellow passion fruit and six variables for purple passion fruit and yellow passion fruit present contrasting differences between them, being the explanatory variables for the purple passion fruit the external and internal color and for the yellow passion fruit length, diameter, and citric acid.